H3K9 Demethylation-Induced R-Loop Accumulation Is Linked to Disorganized Nucleoli - Zhou, Hong; Li, Le; Wang, Qing; Hu, Yan; Zhao, Weiwei; Gautam, Mayank; Li, Lijia (Frontiers in Genetics, 2020)
The nucleolar structure and integrity are pivotal for a range of cellular functions of the nucleoli. It has been shown that cells lacking histone H3 Lysine 9 (H3K9) methylation form fragmented nucleoli. However, the molecular mechanism involved remains poorly understood. Here, we present evidence suggesting that loss of H3K9 dimethylation (H3K9me2) triggers the R-loop accumulation at the rDNA locus, which further leads to the multilobed nucleoli. We reveal that suppression of H3K9 methyltransferase G9a by the inhibitor BIX 01294 causes R-loop accumulation at the rDNA region as well as induces formation of multiple nucleoli. SiRNA-mediated knockdown of RNase H1 that can hydrolyze the RNA chain in R-loops causes an increase in the R-loop formation, which in turn results in multiple nucleoli in one nucleus, whereas H3K9me2 levels are not affected by R-loop accumulation. Inhibition of RNA polymerase I transcription elongation by small molecule inhibitors induces a substantial decrease in H3K9me2 levels, accumulation of R-loops at rDNA sites and nucleolus fragmentation. These results provide mechanistic insight into the role of H3K9me2 in the structural integrity and organization of nucleoli via regulating R-loop accumulation.